The hydraulics of open channel flow : an introduction ; basic principles, sediment motion, hydraulic modelling, design of hydraulic structures - Chanson, Hubert (Elsevier Butterworth Heinemann, 2004)
Since the publication of its first edition in 1999, 'The Hydraulics of Open Channel Flow' has been praised by professionals, academics, students and researchers alike as the most practical modern textbook on open channel flow available. This new edition includes substantial new material on hydraulic modelling, in particular addressing unsteady open channel flows. There are also many new exercises and projects, including a major new revision assignment. This innovative textbook contains numerous examples and practical applications, and is fully illustrated with both colour and black and white photographs. Dr Chanson introduces the basic principles of open channel flow and takes readers through the key topics of sediment transport, hydraulic modelling and the design of hydraulic structures. Comprehensive coverage of the basic principles of key application areas of the hydraulics of open channel flow New exercises and examples added to aid understanding Ideal for use by students and lecturers in civil and environmental engineering.